The Impact Of Customer Empowerment On Reducing Marketing Deception: A Field Study For Several Iraqi Contracting Companies - Y. Hadi*, Mohammed; H. Chitheer, Sadoon (Journal of Economics and Administrative Sciences, 2024)
Purpose: This paper attempts to analyze and discuss the impact of Customer Empowerment (CE) in reducing marketing deceptive practices carried out by companies.Theoretical framework: The literature related to the research topic did not describe of the application of CE in the workplace, as it is a recent variable and is still in the development stage. The scale (Abdel-Bari & Ashry, 2023) was adopted to measure the CE questionnaire, in addition to the scale (Gaber et al., 2018) to measure Marketing Deception (MD). Methodology: Field research was used to understand the practice of CE and identify scams. Six companies specialized in the field of contracting were selected. The research sample consisted of (152) employees. A questionnaire was used to collect data, and hypotheses were tested using the statistical program (SPSS).Results: There is a positive impact of empowering customers in reducing deceptive marketing practices. Research, practical and social implications:Provide a detailed description of the means that can achieve CE and reduce MD. Also, we Provides a practical approach to researching CE and suggests that future research should include business cases as a means of achieving this and provide justification for the importance of implementing CE practices.Originality/value: This paper is among the few to address CE with MD and emphasizes that CE must be an organization-wide goal and requires a long-term commitment to eliminate MD.